Prevalence and Risk Factors for Complications in Patients with Nontransfusion Dependent Alpha- and Beta-Thalassemia. (18th November 2015) - Winichakoon, Poramed; Tantiworawit, Adisak; Rattanathammethee, Thanawat; Hantrakool, Sasinee; Chai-Adisaksopha, Chatree; Rattarittamrong, Ekarat; Norasetthada, Lalita; Charoenkwan, Pimlak
Abstract : Background. Nontransfusion dependent thalassemia (NTDT) is a milder form of thalassemia that does not require regular transfusion. It is associated with many complications, which differ from that found in transfusion-dependent thalassemia (TDT). Currently available information is mostly derived from beta-NTDT; consequently, more data is needed to describe complications found in the alpha-NTDT form of this disease. Methods . We retrospectively reviewed the medical records of NTDT patients from January 2012 to December 2013. Complications related to thalassemia were reviewed and compared. Results . One hundred patients included 60 females with a median age of 38 years. The majority (54 patients) had alpha-thalassemia. Overall, 83 patients had one or more complications. The three most common complications were cholelithiasis (35%), abnormal liver function (29%), and extramedullary hematopoiesis (EMH) (25%). EMH, cardiomyopathy, cholelithiasis, and pulmonary hypertension were more commonly seen in beta-thalassemia. Osteoporosis was the only complication that was more common in alpha-thalassemia. The risk factors significantly related to EMH were beta-thalassemia type and hemoglobin < 8 g/dL. The risk factors related to osteoporosis were female gender and age > 40 years. Iron overload (ferritin > 800 ng/mL) was the only risk factor for abnormal liver function. Conclusion . The prevalence of alpha-NTDT complications was lower and different from beta-thalassemia.